Metode Pembelajaran Tematik Yang Menarik Dalam Program Kampus Mengajar Di Upt Sd Negeri 060889,Medan. - Dina Khatrin Hasibuan; Hairani Siregar; Wasti Tarigan (JOURNAL SAINS STUDENT RESEARCH, 2023)
Teaching Campus is a learning channel that provides opportunities for students to study off-campus for one semester in order to practice their ability to solve complex problems by becoming partners with teachers to innovate in learning, develop strategies and learning models that are creative, innovative and fun. This teaching campus program for students includes being directly involved as teacher partners, principals, and education staff in target schools in developing and implementing learning strategies in schools that are creative, innovative, and fun. Have the opportunity to have experience in exploring various programs according to needs schools, Contribute directly as agents of change in Indonesian education, Sharpen leadership, problem solving, communication skills, analytical thinking, creativity, and innovation directly from the field, Add friendship networks with fellow students in placement schools